Men’s experiences of suicide bereavement: a qualitative study of psychosocial impacts and coping - Karl Andriessen; Nina Logan; Shelley-Anne Ball; Tim De Goey; Dianne Currier; Karolina Krysinska (Frontiers in Public Health)
IntroductionMen bereaved by suicide have an increased risk of adverse psychosocial outcomes, including mental health problems and suicidal behaviour. Despite the potentially strong impact of suicide on their life, little is known of how men experience and cope with grief after suicide. The study aimed to investigate men’s experiences of the psychosocial impacts of and coping with suicide bereavement.MethodsAdhering to the Consolidated Criteria for Reporting Qualitative Research, we designed a study involving semi-structured interviews with a purposive sample (N = 34, Mage = 49.44 years) from across Australia. The transcripts of the interviews were subjected to a codebook thematic analysis.FindingsThe analysis identified three themes: (1) immediate reactions, (2) psychosocial impacts, and (3) psychosocial coping. The findings are underscored by the profound, multifaceted impacts of suicide bereavement, from immediate emotional reactions to long-term mental health effects and trauma. Suicide bereavement frequently disrupted participants’ close relationships and their role as a carer. Participants’ diverse coping strategies included maintaining a bond with the deceased, seeking distraction, or channelling grief into action-oriented approaches. While some potentially maladaptive strategies, such as overworking or substance use, provided temporary relief, other strategies led to personal growth, with some men using their experience to support others or raise awareness about suicide prevention and postvention.ConclusionThe findings indicate that support must focus specifically on men’s experiences of grief after suicide, and appeal to their coping strategies and feelings of responsibility and role as a carer. Further research is urgently needed to establish best practice to support this population, vulnerable to mental health problems and suicidal behaviour.